Career pathways[videorecording] : Two years on (VEA, 2004)
This program provides a fascinating insight into the realities of career development. It is divided logically into five chapter; education and training, work, family, personal development and advice. The students have all changed in the past two years, both in visible and non-visible ways. All have lessons to share and advice to give.